Influence of aerobic fitness level on measured and estimated perceived exertion during exhausting runs - Garcin, M.; Mille-Hamard, L.; Billat, V. (International Journal of Sports Medicine, 2004)
The purpose of the present investigation was 1) to study the effects of fitness level on perceived exertion (RPE) and estimated time limit (ETL) scales during exhausting runs, and 2) to predict time to exhaustion from RPE or ETL values collected during a constant run exercise. Eight high-fitness level and twelve moderate-fitness level endurance trained males performed two exhausting exercises on a 400-m running track. The first test was a graded exercise using a portable metabolic system to determine maximal oxygen uptake (V·O2max), the velocity associated with V·O2max (vV·O2max), the velocity at the lactate threshold (vLT) and the velocity at delta 50 (v?50 : the velocity halfway between vV·O2max and vLT). The second test was a constant run exercise at v?50 to determine the time to exhaustion at this intensity (tlimv?50). Moderate-fitness level athletes perceived exercise to be relatively more strenuous and felt that they could continue for less time than high-fitness level athletes at similar relative velocities. There was no effect of fitness level on perceived exertion for a given relative exercise duration. RPE corresponding to vLT was not statistically significantly different between the two levels groups. For the two groups, measured and predicted exhaustion time values, which were calculated from linear extrapolation of RPE and ETL values collected during the first 4 minutes of a submaximal constant run exercise, were not statistically significantly correlated. These results indicate that the aerobic fitness level seems to influence perceived exertion only during graded exercise. Consequently, if RPE is used to prescribe an exercise intensity, the prescription must be individualised regarding the aerobic fitness level of the athlete except for exercise intensities corresponding to vLT. Moreover, the perceived exertion pattern at the beginning of a submaximal constant run exercise could not be considered as a sensitive predictor of the point of self-imposed exhaustion whatever the fitness level of the athletes.